Integration of Cardiac Actin Mutants Causing Hypertrophic (p.A295S) and Dilated Cardiomyopathy (p.R312H and p.E361G) into Cellular Structures - Erdmann, Constanze (Antioxidants (Basel), 2021)
The human mutant cardiac α-actins p.A295S or p.R312H and p.E361G, correlated with hypertrophic or dilated cardiomyopathy, respectively, were expressed by the baculovirus/Sf21 insect cell system and purified to homogeneity. The purified cardiac actins maintained their native state but showed differences in Ca(2+)-sensitivity to stimulate the myosin-subfragment1 ATPase. Here we analyzed the interactions of these c-actins with actin-binding and -modifying proteins implicated in cardiomyocyte differentiation. We demonstrate that Arp2/3 complex and the formin mDia3 stimulated the polymerization rate and extent of the c-actins, albeit to different degrees. In addition, we tested the effect of the MICAL-1 monooxygenase, which modifies the supramolecular actin organization during development and adaptive processes. MICAL-1 oxidized these c-actin variants and induced their de-polymerization, albeit at different rates. Transfection experiments using MDCK cells demonstrated the preferable incorporation of wild type and p.A295S c-actins into their microfilament system but of p.R312H and p.E361G actins into the submembranous actin network. Transduction of neonatal rat cardiomyocytes with adenoviral constructs coding HA-tagged c-actin variants showed their incorporation into microfilaments after one day in culture and thereafter into thin filaments of nascent sarcomeric structures at their plus ends (Z-lines) except the p.E361G mutant, which preferentially incorporated at the minus ends.